A COMPREHENSIVE SCANNING FOR OPEN, CLOSED AND FILTERED PORTS IN THE COMPUTER SYSTEMS AND NETWORKS: A COMPREHENSIVE SCANNING FOR OPEN, CLOSED AND FILTERED PORTS IN THE COMPUTER SYSTEMS AND NETWORKS - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper a comprehensive scanning for open, closed and filtered ports in the computer systems and networks is made.